1975
DOI: 10.1021/ja00840a009
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-1 and gallium-71 nuclear magnetic resonance study of gallium citrate in aqueous solution

Abstract: Gallium citrate complexes which occur in aqueous solution were studied by and 7lGa NMR and by equilibrium dialysis. In strongly acidic solution low molecular weight complexes having a Ga:citrate ratio of 1:1 form. At pH 2-6 gallium citrate polymers were detected by broadening of the citrate NMR resonance, decrease in the citrate ]H spin-lattice relaxation time, and retardation of the rate of dialysis of the metal. Near neutral pH smaller gallium citrate complexes are observed. Chemical exchange between free an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 3 publications
5
22
0
Order By: Relevance
“…The 1 H and 13 C NMR spectra (400 and 100.6 MHz, respectively) show features in common with certain of the 1 H spectra reported by Glickson et al [20] and the 13 C spectra reported by Chang et al, [21] with the expected better resolution here resulting from the use of higher field spectro- (Table 1) shows two sets of citrate resonances in an approximate ratio 45:55; the slightly weaker group signals occurring at δ ϭ 43.1 (ϪCH 2 Ϫ), 74.7 (ϾCϽ), 175.5 (terminal ϪCH 2 CO 2 ), and 180.6 (central CO 2 ) are assigned to citrate in a GaϪcitrate complex, whereas the slightly stronger signals at δ ϭ 43.6, 73.7, 173.9 and 177.2 are assigned to free citrate. The assignment between free and complexed citrate for these two groups of signals is confirmed by the 13 C shift difference between the two carbonyl signals (3.3 ppm) from a solution of citric acid alone, measured at pH ϭ 1.95.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The 1 H and 13 C NMR spectra (400 and 100.6 MHz, respectively) show features in common with certain of the 1 H spectra reported by Glickson et al [20] and the 13 C spectra reported by Chang et al, [21] with the expected better resolution here resulting from the use of higher field spectro- (Table 1) shows two sets of citrate resonances in an approximate ratio 45:55; the slightly weaker group signals occurring at δ ϭ 43.1 (ϪCH 2 Ϫ), 74.7 (ϾCϽ), 175.5 (terminal ϪCH 2 CO 2 ), and 180.6 (central CO 2 ) are assigned to citrate in a GaϪcitrate complex, whereas the slightly stronger signals at δ ϭ 43.6, 73.7, 173.9 and 177.2 are assigned to free citrate. The assignment between free and complexed citrate for these two groups of signals is confirmed by the 13 C shift difference between the two carbonyl signals (3.3 ppm) from a solution of citric acid alone, measured at pH ϭ 1.95.…”
Section: Resultssupporting
confidence: 86%
“…at pH ϭ 6.4, δ A ϭ 2.58, δ B ϭ 2.44, J AB ϭ 16.9 Hz for the complex, δ A ϭ 2.54, δ B ϭ 2.41, J AB ϭ 15.2 Hz for free citrate). The assignment of these AB signals between complexed and free citrate is confirmed by the values for J AB across the pH range -Glickson et al [20] reported J AB values for free citrate in the range 16.2 to 15.4 Hz between pH ϭ 0.75 and 8.71, and for gallium citrate in the range 16.7 (pH ϭ 0.70) to 17.5 Hz (pH ϭ 7.76). In the intermediate pH range many minor signals appeared in both the 1 H and 13 C spectra which are probably due to various oligomeric complex species.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Presently 67Ga-citrate is the clinically applicable agent best suited to radionuclide tagging. The importance of this agent has prompted 'H and 71Ga nmr studies of gallium citrate complexes in aqueous solutions (14,15), over a range of pH values, in an attempt to shed light on the structure of such complexes with a view to gaining a better understanding of the molecular mechanism of cellular binding of Ga and the inhibition of this process by citrate and other buffers. However, definitive structural data on gallium citrate complexes is lacking and in an effort to determine the mode of coordination of the gallium atoms by citrate species we have prepared two citrate triester complexes incorporating the dimethylgallium moiety.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of a lower natural abundance, 71 Ga is generally the preferred isotope because of its higher 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 (2,(11)(12)16), and C 3 -symmetric Ga-NOTA derivatives (17)(18)(19)(20)(21)(22). As a proof of concept, we have studied here a solution of the approximately octahedral complex Ga-DOTA.…”
mentioning
confidence: 99%